2012
DOI: 10.4172/jbb.1000113
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Bioavailability: Two Pramipexole Formulations in Healthy Volunteers after a Single Dose Administration under Fasting Conditions

Abstract: The study was performed to compare the bioavailability of two Pramipexole 0.125 mg tablet formulations: the test formulation was pramipezan ® (pramipexole) manufactured by Cobalt Pharmaceuticals, Canada/ Arrow Farmacêutica Ltda * . Sifrol ® (Pramipexole) from Boehringer Ingelheim do Brasil Química e Farmacêutica Ltda was used as reference formulation. The study was conducted open with randomized two period crossover design and 8 days wash out period in 48 volunteers of both sexes. Plasma samples were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
(18 reference statements)
1
4
0
1
Order By: Relevance
“…Based on that CV, the use of 22 subjects was adequate to draw a statistical conclusion with the power of no less than 90%. The intra-subject CV of pramipexole obtained from this study was approximately similar to those found in the literature [11,18,19]. …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Based on that CV, the use of 22 subjects was adequate to draw a statistical conclusion with the power of no less than 90%. The intra-subject CV of pramipexole obtained from this study was approximately similar to those found in the literature [11,18,19]. …”
Section: Discussionsupporting
confidence: 88%
“…Using the intra-subject CV of pramipexole from the literature [11], the sample size was estimated by means of confidence intervals (CIs) as tabulated by Diletti et al [17]. There were only 23 subjects who were finally enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Washout period was adequate and there was no quantifiable concentration of the drugs in the second period of the study, indicating that there was no carryover effect from the first to the second period. The mean ratio of parameters C max and AUC 0-t and 90% confidence intervals of correspondents were calculated to determine the bioequivalence [24].…”
Section: Discussionmentioning
confidence: 99%